Genetic Diversity Analysis of Indonesian Pigmented Rice Accessions Based on Functional Molecular Markers - Andari Risliawati; Yusi N. Andarini; Rerenstradika T. Terryana; Kristianto Nugroho; Puji Lestari (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2021)
Pigmented rice is functional staple food that becomes popular because of its anthocyanin content which is beneficial for health. Studies on the diversity of the local variety of Indonesian pigmented rice accessions have been carried out, but are still limited to one region of germplasm origin. This study aimed to analyze the genetic diversity of local varieties of pigmented rice collections of the IAARD-ICABIOGRAD Gene Bank. A total of 93 pigmented rice accessions from 16 provinces in Indonesia were analyzed using 15 functional molecular markers of SSR, STS, and indel. The total alleles detected were 115 with an average per locus of genetic diversity value of 0.71. There were five markers with PIC values >0.75, i.e. RM167, RM223, R8M33, R10M10, and GBSS1. The accessions were divided into two main groups based on their pericarp color. It is necessary to analyze the physicochemical content of the local rice accessions to complement the existing diversity information and identify potential pigmented rice accessions with high palatability.